FORTIFICATION OF PROTEIN HYDRAULIC PROTEIN YELLOW SELAR FISH(Caranx leptolepis) WITH A DIFFERENT AMOUNT TO PEMPEK - Indah, Indah; Dewita, Dewita; Suparmi, Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe purpose of this research was to determine the effect of adding different amounts of protein hydrolyzate of yellow selar (Caranx leptolepis) to pempek and proximate chemical content and sensory quality of pempek with the addition of fish protein hydrolyzate of yellow selar (Caranx leptolepis). The research method used was an experimental method, namely processing pempek by adding different amounts of fish protein hydrolyzate. The research method used was an experimental method, namely processing pempek by adding different amounts of protein hydrolyzate of yellow selar fish. The design used was a non-factorial completely randomized design (CRD) with 4 levels of treatment, namely H0 (without the addition of fish protein hydrolyzate of yellow selar), H1 (addition of 5% yellow selar fish protein hydrolyzate), H2 (addition of 10% yellow selar fish protein hydrolyzate). ) and H3 (addition of 15% yellow selar fish protein hydrolyzate) from the amount of raw material (tapioca flour) each treatment was repeated 3 times, so that the number of experimental units in the study was 12 units. The parameters measured in this study were organoleptic tests (appearance, smell, texture, flavor) and proximate tests (moisture content, ash content, protein content, fat content). The results showed that the organoleptic value of the best treatment in the H3 treatment (addition of 75 mL yellow selar fish protein hydrolyzate) included appearance (slightly grayish color), smell (very fresh typical of yellow selar fish), flavor (slightly salty and typical of yellow selar fish). ), texture (chewy and elastic). Based on the best proximate value is pempek H3 (addition of 75 mL yellow selar fish protein hydrolyzate) including 50.98% water content, 1.29% ash content, 9.25% protein content and 3.02% fat content.Keywords: Fortification, Pempek, yellow selar, Protein Hydrolyzate